2023
DOI: 10.7759/cureus.50524
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21: A More Effective Biomarker Than Free Fatty Acids and Other Insulin Sensitivity Measures for Predicting Non-alcoholic Fatty Liver Disease in Saudi Arabian Type 2 Diabetes Patients

Suhad Bahijri,
Basmah Eldakhakhny,
Sumia Enani
et al.

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is more prevalent among individuals with type 2 diabetes (T2DM), elevating their risk of cardiovascular diseases (CVDs) and premature mortality. There is a need to modify treatment strategies to prevent or delay these adverse outcomes. Currently, there are no sensitive or specific biomarkers for predicting NAFLD in Saudi T2DM patients. Therefore, we aimed to explore the possibility of using fibroblast growth factor 21 (FGF-21), free fatty acids (FFAs), homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…There are various inflammatory biomarkers, particularly cytokines, that have been studied for their potential to prevent and detect CVD at an early stage [4][5][6]. A recent study from Saudi Arabia concluded that FGF-21 can also be used as a marker to predict non-alcoholic fatty liver disease in people with diabetes mellitus type 2 due to its high sensitivity and specificity compared to the other markers [7]. While several researchers have demonstrated a relationship between FGF21 and CVD, its precise role in the pathogenesis of coronary artery disease (CAD) remains unknown [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are various inflammatory biomarkers, particularly cytokines, that have been studied for their potential to prevent and detect CVD at an early stage [4][5][6]. A recent study from Saudi Arabia concluded that FGF-21 can also be used as a marker to predict non-alcoholic fatty liver disease in people with diabetes mellitus type 2 due to its high sensitivity and specificity compared to the other markers [7]. While several researchers have demonstrated a relationship between FGF21 and CVD, its precise role in the pathogenesis of coronary artery disease (CAD) remains unknown [8].…”
Section: Introductionmentioning
confidence: 99%